Insilico molecular docking and ADME/T studies of flavonol compounds against selected proteins involved in inflammation mechanism - Narendra Pentu; Ajitha Azhakesan; Pasupuleti Kishore Kumar (Journal of Applied Pharmaceutical Research)
Background: Using computational tools in drug discovery advanced the research in identifying new drug candidates for the benefit of the pharmaceutical industry and assessing the safety and pharmacokinetic profiles of phytochemicals. Understanding the inflammatory mechanism is not possible, but inflammatory signal transduction by cytokines can be mitigated by using the flavonoid class of drugs like flavonols. Methodology: A molecular docking study of flavonol compounds with proteins linked with inflammation was carried out using the AutodockVina program. SwissADME and pkCSM modules were used to assess the pharmacokinetic features of plant products. Compared to commercially available NSAIDs, flavonols had more excellent molecular docking scores. Results: Calculation of ADME features of flavonols with no carcinogenicity and low oral acute toxicity level. Compared to anti-inflammatory medicines, the Rutin docking score against COX-I (-8.7 kcal/mol) and the Galangin docking score against COX-II enzymes (-9.4 kcal/mol) had higher values. Discussion: Molecular docking studies exhibited the highest docking score for COX-I is Rutin -8.7 Kcal/mol and hydrogen bond with THR-89, PRO-84, LS-468, GLY-471, PHE-470. The highest docking for COX-II is Galangin -9.4 Kcal/mol and hydrogen bonding with VAL-349 and TYR-385. ADME/T studies were performed for all the flavonols. Rutin has the highest violations in drug-likeliness studies.  Conclusion: Flavonols may be more effective anti-inflammatory medicines than commercial medications. By modifying the pharmacokinetic features of plant products through diverse formulation strategies, we can get these phytochemicals to their target sites with fewer adverse effects.